Ethanol and nicotine interaction on liver oxidative status: An experimental study - (:unkn) unknown (Turkiye Klinikleri, 2009)
Objective: To investigate the additive effect of ethanol and nicotine on rat liver oxidative status following either alone or combined sub-chronic administration. Material and Methods: Forty-eight female Sprague Dewley rats were grouped randomly into one of the protocols, which consisted of treatment for 10 days with ethanol 2 g/kg/day (ethanol group, n= 12), nicotine 0.15 mg/kg/day (nicotine group, n= 12), both drugs (ethanol plus nicotine group, n= 12) or saline solution (control group, n= 10) for 10 days. Following 10 days of administration of thesethe above-mentioned agents, malondialdehyde concentration, reduced glutathione concentration and glutathione peroxidase activity were assessed in the liver. Results: The ethanol plus nicotine group had significantly higher malondialdehyde and lower glutathione concentrations than either the ethanol and nicotine and the control groups (both, p< 0.05). The ethanol or nicotine group had significantly higher malondialdehyde concentration and lower glutathione concentration and glutathione peroxidase activity than the control group (all p< 0.05). Malondialdehyde and glutathione concentration was not significantly higher in the ethanol group than in the nicotine group (both, p> 0.05). No significant difference was observed in glutathione peroxidase activity of ethanol, nicotine or ethanol plus nicotine groups (all p> 0.05). Conclusions: Co-administration of ethanol and nicotine results with significant increase in lipid peroxidation and significant decrease in glutathionelevels compared to their separate administration. Copyright © 2009 by Türkiye Klinikleri.
Keywords: Alcohols; Nicotine; Oxidative stress